The private household savings and pensions public in Germany and the United States: Compliance? Lifecycle hypothesis? (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
This paper details how ageing is affecting to private saving and public pensions.In this way, it analyses if Life-Cycle Hypothesis is carrying out for individuals about their saving behaviours and if Pension Public Systems can make them to vary. Forthis reason, it establishes a specifically household saving comparative for Germanyand Unites States, studying also their ageing evolution and pay capacity of publicpension retirement.
Keywords: life–cycle hypothesis; private saving; pension public system; ageing; Germany; United States.